Income tax article 23 in PT Pubagot Jaya Abadi Bengkulu City - Herlin; Sulisti Afriani; Rina Trisna Yanti; Rinto Noviantoro; Neri Susanti (Privietlab, 2021)
Tax is a mandatory contribution given by people to state, one of which is income tax PPh 23. It is a good thing if the taxpayer pays his taxes on time. In this service activity the implementation of service is carried out with the aim of understanding company owners and employees in charge of taxation in carrying out PPh 23 reporting. The methods used in this service include the tutorial method, question and answer and discussion and lectures methods. The results of this stuy are he achievement of understanding of the owners and employees in change of taxation of PPh 23.